2017
DOI: 10.1093/jnen/nlx041
|View full text |Cite
|
Sign up to set email alerts
|

Multisite Assessment of Aging-Related Tau Astrogliopathy (ARTAG)

Abstract: Aging-related tau astrogliopathy (ARTAG) is a recently introduced terminology. To facilitate the consistent identification of ARTAG and to distinguish it from astroglial tau pathologies observed in the primary frontotemporal lobar degeneration tauopathies we evaluated how consistently neuropathologists recognize (1) different astroglial tau immunoreactivities, including those of ARTAG and those associated with primary tauopathies (Study 1); (2) ARTAG types (Study 2A); and (3) ARTAG severity (Study 2B). Microph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 35 publications
2
28
0
Order By: Relevance
“…The occurrence of incidental α-synuclein-positive Lewy bodies and Lewy neurites is increasingly being reported [7, 15, 27, 33, 35] and the 17% prevalence in The 90+ Study is in line with other cohorts without overt parkinsonism. Intriguingly, Lewy pathology was associated with dementia even though there was a weak correlation between the clinical diagnosis of Lewy body disease and Lewy pathology: 12 cases were diagnosed with LBD or AD/LBD, of which only 4 had Lewy pathology.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…The occurrence of incidental α-synuclein-positive Lewy bodies and Lewy neurites is increasingly being reported [7, 15, 27, 33, 35] and the 17% prevalence in The 90+ Study is in line with other cohorts without overt parkinsonism. Intriguingly, Lewy pathology was associated with dementia even though there was a weak correlation between the clinical diagnosis of Lewy body disease and Lewy pathology: 12 cases were diagnosed with LBD or AD/LBD, of which only 4 had Lewy pathology.…”
Section: Discussionmentioning
confidence: 63%
“…ARTAG was also common in this cohort and, to our knowledge, this is the first study to show an association of ARTAG with clinical dementia in a large cohort of elderly individuals [27, 28, 43, 46]. While the importance of CVD and HS is increasingly recognized [20], ARTAG’s clinical relevance has only been suggested in a small cohort of individuals [25].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Recently, argyrophilic and tau‐positive abnormal structures in astrocytes were frequently noted in aged brains, with the new nomenclature of ARTAG proposed . Reports on tau astrogliopathies are increasing . Ferrer et al , found that tau pathology in glial cells largely parallels, but is not identical to, that in neurons in many tauopathies .…”
Section: Discussionmentioning
confidence: 99%